The Gender Gap in Housing Returns - GOLDSMITH‐PINKHAM, PAUL; SHUE, KELLY (Journal of Finance, 2023)
ABSTRACT Using detailed transactions data across the United States, we find that single women earn 1.5 percentage points lower annualized returns on housing relative to single men. Forty‐five percent of the gap is explained by transaction timing and location. The remaining gap arises from a 2% gender difference in execution prices at purchase and sale. Consistent with a negotiation channel, women list for less and experience worse negotiated discounts. The gender gap shrinks in tight markets, where negotiation is replaced by quasi‐auctions. Overall, gender differences in housing explain 30% of the gender gap in wealth accumulation for the median household.